2019
DOI: 10.1111/sed.12653
|View full text |Cite
|
Sign up to set email alerts
|

Are carbonate barrier islands mobile? Insights from a mid to late‐Holocene system, Al Ruwais, northern Qatar

Abstract: Barrier islands are important landforms in many coastal systems around the globe. Studies of modern barrier island systems are mostly limited to those of siliciclastic realms, where the islands are recognized as mobile features that form on transgressive coastlines and migrate landward as sea‐level rises. Barrier islands of the ‘Great Pearl Bank’ along the United Arab Emirates coast are the best‐known carbonate examples. These Holocene islands, however, are interpreted to be anchored by older deposits and immo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 74 publications
0
27
0
Order By: Relevance
“…Most recently, Rivers et al . (2019b) showed that mid‐Holocene deposits are mostly formed of aragonite and calcite (Fig. 3A), and what little dolomite is observed is derived from underlying Eocene rocks.…”
Section: Cenozoic Dolomite Formation In Qatarmentioning
confidence: 99%
See 2 more Smart Citations
“…Most recently, Rivers et al . (2019b) showed that mid‐Holocene deposits are mostly formed of aragonite and calcite (Fig. 3A), and what little dolomite is observed is derived from underlying Eocene rocks.…”
Section: Cenozoic Dolomite Formation In Qatarmentioning
confidence: 99%
“…In Qatar the vast majority of nearshore modern and Holocene sediments are uncemented. Minor exceptions include thin (centimetre‐thick) intervals of cemented/lithified sediments at the base of tidal channels (Shinn, 1973b), or intermittently associated with back barrier mid‐Holocene deposits such as the stromatolites referenced above at Al Ruwais (Rivers et al ., 2019b). The only major exception is beachrock cementation (Fig.…”
Section: Cenozoic Dolomite Formation In Qatarmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of aeolian sand sedimentation of 1-2 mm yr −1 in the upper 3 m of QAT 63 averaged over the time between ca. 7500 and 5800 years ago as inferred from OSL data is driven by two factors: (i) greater sand availability further north (upwind), as large parts of the Qatar peninsula were then still covered by dune fields , and, (ii) at that time, relative sea level, which is coupled with groundwater levels in low-lying areas near the Qatari coast (Macumber, 2011), rose by several metres (Lambeck, 1996), reaching a highstand around 6000 years ago (Perthuisot, 1977;Engel and Brückner, 2014;Parker et al, 2018;Strohmenger and Jameson, 2018;Rivers et al, 2020). A rising groundwater table and capillary fringe stabilize newly deposited sand in dry climates and lead to net accumulation.…”
Section: The Role Of Relative Sea-level Changes In Landscape Formationmentioning
confidence: 99%
“…It seems that after the sea-level highstand phase (+2-3 m, ca. 6000-4500 years ago; Vita-Finzi, 1978;Engel and Brückner, 2014;Parker et al, 2018;Strohmenger and Jameson, 2018;Rivers et al, 2020), deflation began due to the lowering of the groundwater and the capillary fringe along with sea level, thereby affecting the lowering Stokes surface. The characteristic mounds covering specific areas of the Asaila basin (Figs.…”
Section: The Role Of Relative Sea-level Changes In Landscape Formationmentioning
confidence: 99%